Fluctuating superconductivity in organic molecular metals close to the Mott transition. - Nam, MS; Ardavan, A; Blundell, S; Schlueter, J (2007)
On cooling through the transition temperature T(c) of a conventional superconductor, an energy gap develops as the normal-state charge carriers form Cooper pairs; these pairs form a phase-coherent condensate that exhibits the well-known signatures of superconductivity: zero resistivity and the expulsion of magnetic flux (the Meissner effect). However, in many unconventional superconductors, the formation of the energy gap is not coincident with the formation of the phase-coherent superfluid. Instead, at temperatures above the critical temperature a range of unusual properties, collectively known as 'pseudogap phenomena', are observed. Here we argue that a key pseudogap phenomenon-fluctuating superconductivity occurring substantially above the transition temperature-could be induced by the proximity of a Mott-insulating state. The Mott-insulating state in the kappa-(BEDT-TTF)2X organic molecular metals can be tuned, without doping, through superconductivity into a normal metallic state as a function of the parameter t/U, where t is the tight-binding transfer integral characterizing the metallic bandwidth and U is the on-site Coulomb repulsion. By exploiting a particularly sensitive probe of superconducting fluctuations, the vortex-Nernst effect, we find that a fluctuating regime develops as t/U decreases and the role of Coulomb correlations increases.